A bird's eye view of the mental health systems in India - Satish Suhas; Banavaram A. Arvind; Gautham M. Sukumar; Pradeep S. Banandur; Lakshmi P. Nirisha; Channaveerachari N. Kumar; Vivek Benegal; Girish N. Rao; Mathew Varghese; Gopalkrishna Gururaj; NMHS National Collaborators Group (Indian Journal of Psychiatry)
Background: A staggering 85% of the global population resides in low- and middle-income countries (LAMICs). India stands as an exemplary pioneer in the realm of mental health initiatives among LAMICs, having launched its National Mental Health Program in 1982. It is imperative to effectively evaluate mental health systems periodically to cultivate a dynamic learning model sustained through continuous feedback from mental healthcare structures and processes. Materials and Methods: The National Mental Health Survey (NMHS) embarked on the Mental Health Systems Assessment (MHSA) in 12 representative Indian states, following a pilot program that contextually adapted the World Health Organization's Assessment Instrument for Mental Health Systems. The methodology involved data collection from various sources and interviews with key stakeholders, yielding a set of 15 quantitative, 5 morbidity, and 10 qualitative indicators, which were employed to encapsulate the functional status of mental health systems within the surveyed states by using a scorecard framework. Results: The NMHS MHSA for the year 2015–16 unveiled an array of indices, and the resultant scorecard succinctly encapsulated the outcomes of the systems' evaluation across the 12 surveyed states in India. Significantly, the findings revealed considerable interstate disparities, with some states such as Gujarat and Kerala emerging as frontrunners in the evaluation among the surveyed states. Nevertheless, notable gaps were identified in several domains within the assessed mental health systems. Conclusion: MHSA, as conducted within the framework of NMHS, emerges as a dependable, valid, and holistic mechanism for documenting mental health systems in India. However, this process necessitates periodic iterations to serve as critical indicators guiding the national mental health agenda, including policies, programs, and their impact evaluation.